Fuzzy Rough Set Theory for Decision Support Systems - Algarhy, Mohammad Hasan (Journal of Research in Science and Engineering, 2025)
Decision Making is an art of obtaining optimal (sometimes satisfactory) solution of a problem. This procedure may not be always conventional or logical and sometimes it may involve irrational approaches, tacit knowledge, beliefs and faith. In this paper, we deal with the decision-making process when the datum is missing in the information system which possesses fuzzy decision attribute using the concept of rough sets.